2017
DOI: 10.3390/agronomy7010012
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Irrigation Scheduling Using Thermometry on Peach Tree Water Status and Yield under Different Irrigation Systems

Abstract: Abstract:Remotely-sensed canopy temperature from infrared thermometer (IRT) sensors has long been shown to be effective for detecting plant water stress. A field study was conducted to investigate peach tree responses to deficit irrigation which was controlled using canopy to air temperature difference (∆T) during the postharvest period at the USDA-ARS (U.S. Department of Agriculture, Agricultural Research Service) San Joaquin Valley Agricultural Sciences Center in Parlier, California, USA. The experimental si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…In all years studied, the differences between the yields of the irrigated peach trees and the yields of the non-irrigated ones were statistically very significant. Obtained contents are similar to those from previous studies (Chalmers et al, 1981;Zhang et al, 2017).…”
supporting
confidence: 78%
“…In all years studied, the differences between the yields of the irrigated peach trees and the yields of the non-irrigated ones were statistically very significant. Obtained contents are similar to those from previous studies (Chalmers et al, 1981;Zhang et al, 2017).…”
supporting
confidence: 78%
“…The following thermal-based indexes were calculated throughout the experiment: Tc − Ta: the difference between the canopy and the surrounding air temperature. CWSI (Crop Water Stress Index): calculated empirically according to the equation described by Idso et al [ 11 ]: where, (Tc − Ta)LL and (Tc − Ta)UL correspond to the lower and upper limit, respectively. The lower limit (LL) was calculated for a given vapor pressure deficit (VPD), from the Non-Water Stressed Baseline (NWSB), which is equivalent to a canopy transpiring at the potential rate (fully irrigated trees with fully open stomata).…”
Section: Methodsmentioning
confidence: 99%
“…CWSI (Crop Water Stress Index): calculated empirically according to the equation described by Idso et al [ 11 ]:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies addressing the effect of deficit irrigation on peach fruit quality either refer to an improvement of it [71] or no effect [134,136]. Pérez-Sarmiento et al [138] applying several RDI strategies to apricot have found improvements in some qualitative characteristics of the fruits, such as the level of soluble solids, sugar/ acid ratio, and fruit color, without negative effects in yield.…”
Section: Effect On Fruits Qualitymentioning
confidence: 99%